Africa’s economy grows, but many stomachs empty - Kingsley Ighobor (Africa Renewal, 2014)
Each year, governments, journalists, development experts and others look forward to the United Nations Development Programme’s Human Development Report. The report includes a ranking of countries based on life expectancy, literacy, quality of life and so on. Once it is released, governments and citizens of countries with high rankings immediately trumpet their achievements. Those with lower rankings, such as the Democratic Republic of the Congo, which was last in 2013 in Africa, come in for criticism.